Challenges to civil rights guarantees in India - Noorani, Abdul Gafoor Abdul Majeed, 1930-; South Asia Human Rights Documentation Centre (Oxford : Oxford University Press, 2012)
This collection of essays examines the civil rights guarantees as enshrined in the Constitution of India. As evident in the State's handling of contemporary social and political issues, it analyses the challenges faced by the Indian civil rights framework.
Description based on online resource; title from PDF title page (viewed on Sept. 4, 2012).
Includes bibliographical references and index.
Keywords: Civil rights -- India; Constitutional law -- India